Immunomodulatory potential of Nisin A with application in wound healing - Mouritzen, Michelle V.; Andrea, Athina; Qvist, Katrine; Poulsen, Steen S.; Jenssen, Håvard (Wound repair and regeneration, 2019)
Antimicrobial peptides can have a dual role with both antimicrobial activity against a broad range of bacteria and immunomodulatory effect, making them attractive as therapeutic treatment of difficult wounds. Nisin A is widely known for its antimicrobial activity, and a preliminary study demonstrated that it increased wound closure, but the mechanism behind its effect is unknown. The aim of this study is to elucidate the wound healing potential of Nisin A and the mechanism behind. First, an epithelial and endothelial cell line, human keratinocyte (HaCaT) and human umbilical vein endothelial cell, were used to demonstrate migration and proliferation effects in vitro. From HaCaT cells and peripheral blood mononuclear cell, changes in cytokine levels were shown by quantitative polymerase chain reaction and enzyme‐linked immunosorbent assay. Second, the ex vivo porcine wound healing model was used to investigate the re‐epithelization potential of Nisin A. Finally, the model Galleria mellonella was used to confirm antimicrobial activity and to investigate potential immunomodulatory effects in vivo. Here, we demonstrated that Nisin A affected migration significantly of both human umbilical vein endothelial cell and HaCaT cells (p < 0.05) but not proliferation, potentially by decreasing the levels of proinflammatory cytokines tumor necrosis factor‐α, interleukin‐6, and interleukin‐8 (p < 0.001). Furthermore, Nisin A treatment diminished lipopolysaccharide‐induced tumor necrosis factor‐α levels from peripheral blood mononuclear cells and monocyte chemoattractant protein‐1 from HaCaT cells (p < 0.001). Furthermore, Nisin A did not affect proliferation ex vivo either but increased re‐epithelization of the porcine skin. Nisin A improved survival of G. mellonella significantly from Staphylococcus epidermidis (p < 0.001) but not from Escherichia coli, indicating that Nisin A did not help the larvae to survive the infection in a different than direct antimicrobial way. All together this makes Nisin A a potential treatment to use in wound healing, as it increases the mobility of skin cells, dampens the effect of lipopolysaccharide and proinflammatory cytokines, and decreases bacterial growth.